Smart Policing Strategy in Efforts to Eradicate Illegal Online Loan Cases (Pinjol) through the Establishment of an Investment Alert Task Force (SWI) - Mulya Adhirama; Chairul Muriman Setyabudi; Surya Dharma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The rise of online loans (pinjol) from fintech peer to peer (P2P) occurs due to inevitable technological development. The number of complaints submitted to the Jakarta Legal Aid Institute (LBH) has more than doubled in 6 months. Based on data from LBH Jakarta, there were 4,500 complaints regarding fintech lending as of June 2019. This figure increased from the number of complaints as of early December 2018 which was 1,330 complaints. Due to the fact that many complaints of illegal loans victims, the establishment of cooperation with several relevant agencies including the Indonesian National Police (Polri) formed an Investment Alert Task Force (SWI) to tackle and prevent illegal online loans. This study uses a qualitative case study approach to analyze the negative effects of this phenomenon and answer question related to the strategy of the Indonesian National Police (Polri) through the implementation of Smart policing as an effort to overcome and prevent online loan-based crimes.